Identification, Heritability, and Relation With Gene Expression of Novel DNA Methylation Loci for Blood Pressure. Issue 1 (July 2020) - Huang, Yisong; Ollikainen, Miina; Muniandy, Maheswary; Zhang, Tao; van Dongen, Jenny; Hao, Guang; van der Most, Peter J.; Pan, Yue; Pervjakova, Natalia; Sun, Yan V.; Hui, Qin; Lahti, Jari; et al.
Abstract : We conducted an epigenome-wide association study meta-analysis on blood pressure (BP) in 4820 individuals of European and African ancestry aged 14 to 69. Genome-wide DNA methylation data from peripheral leukocytes were obtained using the Infinium Human Methylation 450k BeadChip. The epigenome-wide association study meta-analysis identified 39 BP-related CpG sites with P <1×10 −5 . In silico replication in the CHARGE consortium of 17 010 individuals validated 16 of these CpG sites. Out of the 16 CpG sites, 13 showed novel association with BP. Conversely, out of the 126 CpG sites identified as being associated ( P <1×10 −7 ) with BP in the CHARGE consortium, 21 were replicated in the current study. Methylation levels of all the 34 CpG sites that were cross-validated by the current study and the CHARGE consortium were heritable and 6 showed association with gene expression. Furthermore, 9 CpG sites also showed association with BP with P <0.05 and consistent direction of the effect in the meta-analysis of the Finnish Twin Cohort (199 twin pairs and 4 singletons; 61% monozygous) and the Netherlands Twin Register (266 twin pairs and 62 singletons; 84% monozygous). Bivariate quantitative genetic modeling of the twin data showed that a majority of the phenotypic correlations between methylation levels of these CpG sites and BP could be explained by shared unique environmental rather than genetic factors, with 100% of the correlations of systolic BP with cg19693031 ( TXNIP ) and cg00716257 ( JDP2 ) determined by environmental effects acting on both systolic BP and methylation levels. Abstract : Supplemental Digital Content is available in the text.